Human development :why the capability approach matters more than ever and how it can make a difference - Pule, Ramakwe Nicholus (My University, 2018)
Aristotle, Amartya Sen and Martha Nussbaum, amongst others argue that political philosophy has its inception in ethics. These political theorists get to the heart of political philosophy, tackling questions such as: what kind of life is the good life for human beings? What kind of life is proper for a person amongst people? This research paper has a similar interest in analyzing the conceptual ‘glue’ between political philosophy and ethics, but its goal is not to seek to examine the aforementioned questions in great detail. The question this research paper focuses on is this: what should we look at, when evaluating whether a person’s state of affairs is more or less just compared to another? Political theorists, economists, and philosophers have in the diverse periods in history debated what proper metric of ethical judgements must be used to evaluate whether a person’s state of affairs is more or less just compared to another? In other words, political theorists, economists, and philosophers have sought to answer the aforementioned question by providing comprehensive approaches for making ethical judgements to measure human development and human well-being. This research paper will therefore distinguish various approaches in order to decide which, if any, of these approaches provide an attractive political ideal, through which a proper systematic study of ethical judgements in the measurement of human development and human well-being can be conducted. To cope with this diversity, there is a clear need to study three approaches concerned with dimensions of understanding human development and human well-being. To take a few examples: the welfarist approach asserts that the good of individuals must almost invariably be judged by their preference (an expression of utility), leaving aside the ethical judgements of the individual preferences of the people who constitute a society; the resourcist approach asserts that we should compare the holding of resources, omitting what individuals, possessed of diverse abilities, and preferences, can do with these resources; and the capability approach asserts that instead of looking at people’s holding of resources and prospects for preference, we should look at what kinds of functionings and capabilities they are able to achieve. Therefore, the question becomes: should we evaluate individual preferences, holdings of resources, or functionings and capabilities? This research paper seeks to compare and contrast these approaches, by confronting the views of political and economics theorists – some more supportive of the individual preferences metric, some more supportive of the holding of the resources metric, and some more supportive of functionings and capabilities metric. Notwithstanding that these approaches have serious limitations, and that while they fail in rather different and contrasting ways, the concern of this research paper is not about which approach is superior, but rather about which approach can deliver the most plausible conditions for making ethical judgements to measure human development and human wellbeing. Therefore, this research paper will defend the capability approach as an alternative for, and improvement on, the welfarist and resourcist approaches.
Dissertation submitted in partial fulfilment of the requirements for the degree of Master of Arts in Political Studies at the University of the Witwatersrand, 2018
Keywords: Political science--Philosophy; Political science--Ethics; Political science